Hubungan Kualitas Pelayanan Kesehatan dengan Kepuasan Pasien Jaminan Kesehatan Nasional (JKN) di Unit Rawat Inap Puskesmas Dumai Barat - Ratih Ayuningtyas (Universitas Ahmad Dahlan, 2019)
In order to improve the health status of the Indonesian people, the government has organized a national health insurance program (JKN) for the health of individuals through the social security organizing body (BPJS). The program doesn’t involve various stakeholders, one of which is the Puskesmas. However, until now there are still many complaints arising from the administration of JKN, one of which is the quality of health services that haven’t been good. Quality of health services affect patient satisfaction. The better the quality of services provided, the better patient satisfaction and vice versa. Inpatient care is one of the facilities obtained by Puskesmas that has an inpatient room in the city of Dumai since 2016. To find out the relationship between the quality of health service and the level of satisfaction of JKN patients in the inpatien unit of Dumai Barat health center Puskesmas. Using an analytic observational study design, with a cross sectional study design. The sampling technique is done by quota sampling with a sample size of 30 people and statistically tested using the Spearman correlation test. In this study there was a relationship between the quality of health services with patient satisfaction of JKN in the inpatient unit of the Dumai Barat health center Puskesmas with a correlation coefficient of 0,343 and p-value 0,032. Conclusion: There is a relationship between the quality of health service and the satisfaction of JKN in the inpatient unit of the Dumai Barat health center Puskesmas.